Nutrition interventions integrated into an existing maternal, neonatal, and child health program reduce food insecurity among recently delivered and pregnant women in Bangladesh. - Frongillo, Edward A; Nguyen, Phuong H; Sanghvi, Tina; Mahmud, Zeba; Aktar, Bachera; Alayon, Silvia; Menon, Purnima (Oxford Academic, 2022)
This article was published in The Journal of Nutrition [C 2019 American Society for Nutrition. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/), ] and the definite version is available at: https://doi.org/10.1093/jn/nxy249 The Journal's website is at: https://academic.oup.com/jn/article/149/1/159/5288239